'I (don't) want X/Y': Formulating 'wants' in Chinese Mediation Resources. (October 2022) - Ke, Xianbing
The recurrent court-related mediation discourse studies have focused on mediation participants' willingness. Drawing on a corpus of five situated recorded court-related civil mediation data in China, this article takes one of the frequently-used mediation resources ' I don't want X/Y ' (here X, Y stands for a certain mediation willingness/intention) as a case study of formulating mediation 'wants'. It is intended to explore mediation participants' exploitation of the court-related mediation resources to express their mediation willingness/ intentions: how the mediator manipulates either side of the participants' mediation discursive concepts; how the mediator shift the trajectory of narrating the participants' mediation dispute-facts to judging on the dispute-facts; and how the mediator deviates himself from the third-party neutral mediators' mediating role. The value of analyzing this formulation ' I don't want X/Y ' is to reveal the fact that such mediation practices in their recurrent environments might go against the court-related mediation principles such as being self-willingness, neutrality and uprightness. This article contributes to formulate mediation 'wants' strategically and promote the court-related mediation practices in the service of sequentially unfolding mediation interaction effectively.